The impact of the introduction of direct oral anticoagulants into a general practice and hospital anticoagulant services: two local service evaluations. Issue 6 (2nd June 2019) - Cahill, Tom; Broughton, Julie; Ferguson, Thomas; Jenkins, Stephen
Abstract : Background/Aims: Anticoagulants are indicated for stroke prevention in nonvalvular atrial fibrillation, and treatment and prevention of venous thromboembolism. The aim of this study was to describe the impact of introducing direct oral anticoagulants on anticoagulation services. Methods: One primary and one secondary care anticoagulation service evaluation compared pre-direct oral anticoagulant (2012) and post-direct oral anticoagulant introduction (2015). Findings: In the secondary care service, anticoagulant monitoring clinics decreased by 20% and service capacity increased by 38.5% post-direct oral anticoagulant introduction. Direct oral anticoagulants comprised 87.6% of newly-initiated anticoagulants post-direct oral anticoagulant introduction. In patients newly initiated on anticoagulation, a total of 62 anticoagulation-related inpatient admissions were recorded in 12.6% of patients in the pre-direct oral anticoagulant period, compared with a total of 21 anticoagulation-related admissions in 3.6% of patients in the post-direct oral anticoagulant period. In the primary care service, warfarin comprised 62.9% of all anticoagulants prescribed post-direct oral anticoagulant introduction. Overall, patients attended a mean of 14.2 anticoagulation service visits in 6 months pre-direct oral anticoagulant and 13.3 visits in 6 months post-direct oral anticoagulant introduction (non-direct oral anticoagulant-treated: 16.1/patient; direct oral anticoagulant treated: 0.8/patient). Few patients were offered a choice of anticoagulant; however, overall patient satisfaction was high in both services. Conclusions: Direct oral anticoagulant introduction in secondary care was associated with increased service capacity and decreased patient visits. Patient choice was limited; however, satisfaction was high in both services.